2013
DOI: 10.3844/ajbbsp.2013.195.205
|View full text |Cite
|
Sign up to set email alerts
|

DYNAMIC MATHEMATICAL MODELLING OF REACTION KINETICS FOR CYCLODEXTRINS PRODUCTION FROM DIFFERENT STARCH SOURCES USING <i>BACILLUS MACERANS</i> CYCLODEXTRIN GLUCANOTRANSFERASE

Abstract: This study relates to the mathematical modelling of enzymatic production of Cyclodextrins (CDs) by Cyclodextrin Glucanotransferase (CGTase) from Bacillus macerans. The experiments were carried out in batch mode using different starch sources and the results were used to estimate unknown parameters using linearization and dynamic simulation methods. α- and β-CD produced from tapioca were found to give the highest Michaelis-Menten constant, KM,i of 58.23 and 54.07 g L-1, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Kelly et al ( 2008 ) reported values ranging from 3.0 × 10 −3 /s to 329/s for CGTases produced with CS as carbon source. The CGTase from B. megaterium , using AS as substrate in this work, is in agreement with the Kcat values published elsewhere (Shahrazi et al, 2013 ; Usharani et al, 2014 ). CDs are produced by the catalytic action of CGTase through an intramolecular transglycosylation reaction.…”
Section: Discussionsupporting
confidence: 92%
“…Kelly et al ( 2008 ) reported values ranging from 3.0 × 10 −3 /s to 329/s for CGTases produced with CS as carbon source. The CGTase from B. megaterium , using AS as substrate in this work, is in agreement with the Kcat values published elsewhere (Shahrazi et al, 2013 ; Usharani et al, 2014 ). CDs are produced by the catalytic action of CGTase through an intramolecular transglycosylation reaction.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of α-CD forming for 1 hour shows drastically increased up to 28 % of production yield and gradually increases up to 48 % after 8 hours of reaction time, as presented in Figure 2. Substrate limitation and product inhibition probably effected to the enzymatic reaction of CGTase, indicating stationary line when the reaction process time was extended [24]. Fig.…”
Section: Cgtase Immobilizationmentioning
confidence: 91%
“…Because these molecules can form inclusion complexes with many compounds, they are widely used in the food, pharmaceutical, cosmetic, and chemical industries . In the last years, there has been a progressive increase in the number of publications and patents related to the production of CDs . Because the purification of α‐ and γ‐CDs considerably increases the cost of production, 97% of the CDs used in the market are β‐CDs .…”
Section: Introductionmentioning
confidence: 99%